Notice of the Devastations effected by Scottish Raids into Northumberland, in the 14th Century (Proceedings of the Society of Antiquaries of Scotland, 1854)
A translated letter was presented on behalf of corresponding member Mr John Fenwick. The letter was from the Bishop of Durham to the monastery at Hexham on behalf of Lord Henry Percy, Earl of Northumberland. The letter concerns a petition the monastery sent asking for help with the dangers presented by the Scots' frequent invasions of the area. The Earl of Northumberland agrees to provide for the petitioners.